Cannabinoid Hyperemesis Syndrome: A Case Report and Review of Pathophysiology - Iacopetti, Corina L. (Clin Med Res, 2014)
Cannabis is the most widely used illicit drug in the United States, with lifetime prevalence of use estimated at 42% to 46%. The antiemetic properties of cannabis are well-known by the medical community and the general public; however, less well-recognized is the paradoxical potential for certain chronic users to develop hyperemesis. We describe in this case a patient with prior extensive work-up for nausea and vomiting and previous diagnosis of cyclic vomiting syndrome who presented with characteristic features of cannabinoid hyperemesis syndrome. We review the current literature for this condition and highlight potential mechanisms for its pathogenesis.